Inhibition of interleukin-6 abolishes the promoting effects of pair housing on post-stroke neurogenesis. (29th October 2015) - Meng, C.; Zhang, J.-C.; Shi, R.-L.; Zhang, S.-H.; Yuan, S.-Y.
Graphical abstract: Highlights: Interleukin (IL)-6 maintained and promoted post-stroke neurogenesis. Pair housing (PH) promoted neurogenesis and functional recovery through IL-6. PH increased IL-6 levels by inhibiting calpain activity during stroke recovery. Calpain-IL-6 pathway played key roles in PH-induced functional recovery. Abstract: Interleukin-6 (IL-6) has been shown to promote post-stroke angiogenesis and long-term functional recovery; however, whether IL-6 could promote post-stroke neurogenesis remains unclear. This study aims to investigate the effects of IL-6 on neurogenesis after ischemic stroke. We also investigated whether pair housing (PH) could improve the experimental stroke outcome through IL-6. Transient middle cerebral artery occlusion (tMCAO) was induced in mice treated with recombinant IL-6 (rIL-6) or anti-IL-6 neutralizing antibodies (anti-IL-6 mAbs). Another set of mice were pair-housed (PH; male and ovariectomized female) for 2 weeks, subjected to tMCAO and then assigned to a housing condition (isolated or PH). Pair-housed mice were treated with anti-IL-6 mAbs. Behavioral assessments were made 3 days before tMCAO and after 28 days of reperfusion. Neural progenitor cells (NPCs) isolated from ipsilateral subventricular zone (SVZ) at 14 days post-ischemia were treated with rIL-6 plus soluble IL-6 receptor (sIL-6R). The effects of IL-6 on the proliferation and differentiation of NPCs were examined in vivo and in vitro . The role and mechanism of IL-6 in PH-mediated enhancement of NPC proliferation and functional recovery were investigated in vivo . We found that anti-IL-6 mAbs significantly reduced the proliferation and neuronal differentiation of NPCs in the ipsilateral SVZ, as well as functional recovery; whereas rIL-6 conferred the opposite effects. PH significantly promoted NPC proliferation and functional recovery compared with socially isolated cohorts; blockade of IL-6 with anti-IL-6 mAbs prevented this promoting effect. In conclusion, our results suggest that IL-6 is an important mediator of social interaction on neurogenesis and long-term functional recovery after ischemic stroke.